Azhari, Ainul STUDI LITERATUR TENTANG DIGITALISASI HADIS DAN TANTANGAN PENDIDIKAN ISLAM DI ERA TEKNOLOGI - Ainul Azhari (ISLAMIKA, 2023)
This research aims to comprehensively examine the process of digitizing hadith and its implications for Islamic education in the technological era. Using a literature review approach, this research explores various academic sources?including journals, books, and digital hadith repositories?to analyze how digital transformation impacts the way Muslims interact with, understand, and teach hadith. The results of the study indicate that digitizing hadith has broadened access to religious knowledge, increased learning efficiency, and strengthened the study of sanad and matn through digital tools. However, on the other hand, serious challenges arise in the form of source validity, data authenticity, and the decline of the authority of scholars in online learning. Islamic education needs to develop Islamic digital literacy to utilize technology without losing epistemological depth and scientific etiquette.